PENGARUH KONSELING TERHADAP SIKAP KLIEN VCT TENTANG HIV/AIDS DI PUSKESMAS MENTIKAN KOTA MOJOKERTO - Dwi w, Binarti; Akbar, Amar (JURNAL KEPERAWATAN SEHAT, 2013)
PENGARUH KONSELING TERHADAP SIKAP KLIEN VCT TENTANG HIV/AIDS DI PUSKESMAS MENTIKAN KOTA MOJOKERTOBy :Faisal Ibnu,Binarti Dwi W,Amar AkbarSTIKES BINA SEHAT PPNI MOJOKERTOInfectious diseases HIV / AIDS is a health problem in Indonesia. Lack of promotion of the public about the existence of VCT ( Voluntary Counseling and Testing ) , and the difficulty of the community to access VCT services . The purpose of this study is to prove the effect of counseling on poly VCT clients attitudes about HIV / AIDS at the Health Center Mentikan Mojokerto . In this study using pre - experimental research design . Independent variables are counseled on HIV - AIDS and the dependent variable is the attitude of the client poly VCT on HIV - AIDS . The population in this study are individuals who have behavioral risk of contracting HIV AIDS who visited the health center Mentikan number 28 , the sampling technique used was obtained 28 samples of consecutive sampling . The instrument used was a questionnaire / questionnaires . Results of research on attitudes prior to counseling the majority of respondents had a negative attitude that is 16 respondents ( 57 % ) . Performed after counseling while most respondents have a positive attitude that is 24 respondents ( 86 % ) . From the data analysis using the Wilcoxon signed ranks test test results obtained ρ = 0.001 while α = 0.05 . Value ρ < α , then H0 is rejected and H1 is accepted . There is the effect of counseling on clients attitudes poly VCT on HIV / AIDS at the Health Center Mentikan Mojokerto . Of this research is there influence clients attitudes toward counseling poly VCT on HIV / AIDS at the Health Center Mentikan Mojokerto . With the counseling or counseling have an influence on the attitude from negative to positive , but still there are not affected this can be caused by low levels of educationand life experienceis still minimal .Keywords : Counseling , Client Attitudes VCT , HIV / AIDS